2017
DOI: 10.1002/rcm.7986
|View full text |Cite
|
Sign up to set email alerts
|

"Bottom‐up" in situ proteomic differentiation of human and non‐human haemoglobins for forensic purposes by matrix‐assisted laser desorption/ionization time‐of‐flight tandem mass spectrometry

Abstract: The MALDI-TOF-MS-based in situ "bottom-up" proteomic methodology described here shows great promise for the detection of human blood and even imaging of blood in bloodied fingermarks. The approach is sensitive, can differentiate between human blood and that from many animals (including several Australian native animals), and can be implemented after traditional crime scene fingermark enhancement techniques have been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Since 2014, huge analytical efforts have been also put into the reliable detection of blood in both stains and fingermarks [16][17][18][19] , since its detection is crucial for the crime scene dynamics reconstruction within violent crimes including murders (especially with no body).…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2014, huge analytical efforts have been also put into the reliable detection of blood in both stains and fingermarks [16][17][18][19] , since its detection is crucial for the crime scene dynamics reconstruction within violent crimes including murders (especially with no body).…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
“…Although this method of detecting blood is more specific, specificity can be further increased to the application of a bottom up proteomic approach in combination with MALDI MS 17,18 .…”
Section: What Information Can Be Obtained Through the Application Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of multiple blood-specific proteins is a more specific approach compared to those previously described as, although HB is specific to blood, it may be found as a trace contaminant in other biofluids. Furthermore, Bradshaw et al 8 Patel et al 9 and Kamanna et al 10 demonstrated the possibility to determine blood provenance which can be valuable in an investigation.…”
mentioning
confidence: 99%
“…KEYWORDS: forensic science, contact trace, brass cartridge, tape collection, protein DNA co-extraction With advanced instrumentation and data analysis software proteomics is not only a rising field in clinical and basic research, but has also yielded several forensic applications. Protein mass spectrometry has been successfully employed for body fluid, tissue, and species identification (1)(2)(3)(4)(5)(6), with some applications even pursuing in situ detection (7,8). Human proteins are known to exhibit genetic differences between individuals with amino acid sequence changes representing the corresponding nonsynonymous single nucleotide polymorphisms (nSNPs) at the DNA level.…”
mentioning
confidence: 99%